Rheumatoid arthritis in an urban South African Negro population. Issue 2 (April 1975) - Solomon, L; Robin, G; Valkenburg, H A
Abstract : (1) An epidemiological study of an urban South African Negro community has been carried out in Johannesburg. Altogether 964 respondents were examined and in each case radiographs of the hands and feet were obtained. Rheumatoid factor tests were carried out on 404 serum samples. (2) Rheumatoid arthritis (RA) was graded 'definite' or 'probable' on the basis of a modification of the Rome criteria (Kellgren, Jeffrey, and Ball, 1963a). (3) In marked contrast to the findings in rural Africans the prevalence of RA in this community was similar to that in Caucasian populations. Five respondents (all elderly women) had 'definite' RA, giving a prevalence of 1.4% of the females and 0.9% of the total population sample over 15 years old. The prevalence of 'definite' and 'probable' RA combined was 2.6% for males, 3.7% for females, and 3.3% for all individuals over 15 years old. Prevalence increased with age, reaching a maximum in the 65- to 74-year cohort. (4) The form and severity of the clinical and radiological features were unlike the mild manifestations seen in rural African peoples and closely resembled the usual clinical picture of rheumatoid disease. (5) The latex fixation test was positive in 12.1% of the sera tested, which is similar to the high titres found in other African populations. No obvious cause for this phenomenon was found. (6) Several reasons for the marked difference in prevalence of RA between this urban African population and a rural African population are considered. Marked intraracial differences such as this point to the importance of sociological and environmental factors in the pathogenesis of rheumatoid arthritis.